Hemojuvelin is a novel suppressor for Duchenne muscular dystrophy and age‐related muscle wasting. Issue 3 (18th March 2019) - Zhang, Peng; He, Jian; Wang, Fei; Gong, Jing; Wang, Lu; Wu, Qian; Li, Wenjiong; Liu, Hongju; Wang, Jing; Zhang, Kunshan; Li, Mao; Huang, Xusheng; et al.
Abstract: Background: Muscle wasting occurs in response to various physiological and pathological conditions, including ageing and Duchenne muscular dystrophy (DMD). Transforming growth factor‐β1 (TGF‐β1) contributes to muscle pathogenesis in elderly people and DMD patients; inhibition of TGF‐β1 signalling is a promising therapeutic strategy for muscle‐wasting disorders. Hemojuvelin (HJV or Hjv as the murine homologue) is a membrane‐bound protein that is highly expressed in skeletal muscle, heart, and liver. In hepatic cells, Hjv acts as a coreceptor for bone morphogenetic protein, a TGF‐β subfamily member. The aim of this study was to investigate whether Hjv plays an essential role in muscle physiological and pathophysiological processes by acting as a coreceptor for TGF‐β1 signalling. Methods: Conventional and conditional Hjv knockout mice as well as mdx and aged mice transfected with Hjv overexpression vector were used to study the role of Hjv in muscle physiology and pathophysiology. qRT‐PCR, western blotting, and immunohistochemistry examinations were conducted to evaluate gene, protein, and structural changes in vivo and in vitro . Exercise endurance was determined using treadmill running test, and muscle force was detected by an isometric transducer. RNA interference, immunoprecipitation, and dual‐luciferase reporter assays were utilized to explore the mechanism by which Hjv regulates TGF‐β1 signalling in skeletal muscle. Results: Conventional and conditional Hjv knockout mice displayed muscle atrophy, fibrosis, reduced running endurance, and muscle force. HJV was significantly down‐regulated in the muscles of DMD patients ( n  = 3, mean age: 11.7 ± 5.7 years) and mdx mice as well as in those of aged humans ( n  = 10, 20% women, mean age: 75.1 ± 9.5 years) and mice. Overexpression of Hjv rescued dystrophic and age‐related muscle wasting. Unlike its function in hepatic cells, the bone morphogenetic protein downstream phosphorylated p‐Smad1/5/8 signalling pathway was unchanged, but TGF‐β1, TGF‐β receptor II (TβRII), and p‐Smad2/3 expression were increased in Hjv‐ deficient muscles. Mechanistically, loss of Hjv promoted activation of Smad3 signalling induced by TGF‐β1, whereas Hjv overexpression inhibited TGF‐β1/Smad3 signalling by directly interacting with TβRII on the muscle membrane. Conclusions: Our findings identify an unrecognized role of HJV in skeletal muscle by regulating TGF‐β1/Smad3 signalling as a coreceptor for TβRII. Unlike the TGF‐β1/Smad3 pathway, HJV could be a reliable drug target as its expression is not widespread. Novel therapeutic strategies could potentially be devised to interfere only with the muscle function of HJV to treat DMD and age‐related muscle wasting.